Overall survival in patients with metastatic melanoma. (May 2015) - Song, Xue; Zhao, Zhongyun; Barber, Beth; Farr, Amanda M.; Ivanov, Boris; Novich, Marilyn
Abstract Introduction: Patients with regionally or distantly metastatic melanoma have poor long-term prognosis. The objective of this analysis was to describe survival rates among patients diagnosed with unresectable stage IIIB/C or stage IV melanoma. Methods: Using data from the Surveillance, Epidemiology, and End Results (SEER) database, patients diagnosed with unresectable stage IIIB/C and stage IV (M1a, M1b, M1c) melanoma between 2004 and 2009 were selected. Patients' demographic and clinical characteristics were reported at the time of diagnosis. The outcome of the analysis was time from melanoma diagnosis to death. Survival was presented as 1 year, 2 year, and 3 year survival rates, and median overall survival. Results: A total of 1682 patients met the study criteria, with 4.4% at stage IIIB/IIIC, 12.6% at M1a, 17.4% at M1b, and 65.6% at M1c. The mean age was 64 years, 49.5% of patients were 64 years old or younger, 68.0% were male, and 91.7% were white. Patients at stage IIIB/IIIC had a median overall survival (OS) of 24.3 months, with a survival rate of 67.2% at 1 year, 42.9% at 2 years, and 32.1% at 3 years. For patients at stage M1a, the median OS was 22.3 months, 1 year, 2 year, and 3 year survival rates were 64.5%, 40.4%, and 26.4%, respectively; for patients at stage M1b, median OS was 11.2 months, 1 year, 2 year, and 3 year survival rates were 43.8%, 23.4%, and 13.8%, respectively; for patients at stage M1c, median OS was 5.1 months, and 1 year, 2 year, and 3 year survival rates were 22.3%, 8.9%, and 4.7%, respectively. Conclusions: Among patients diagnosed with unresectable metastatic melanoma from 2004 to 2009, patients at later stages had lower median overall survival and higher mortality rates than patients at earlier stages. Limitations of this analysis include the lack of information on disease progression, therapies used, and genetic factors.